2020
DOI: 10.1002/mar.21386
|View full text |Cite
|
Sign up to set email alerts
|

Self‐concept, individual characteristics, and counterfeit consumption: Evidence from an emerging market

Abstract: The study draws on a sample of over 350 consumers from 10 department stores in an emerging market where counterfeit products are available in abundance and there is a huge demand for such goods. The findings reveal that interdependent and independent self traits significantly affect individual characteristics, that is, susceptibility to normative influence, readiness to take social risk, and status acquisition (SA), which in turn influences counterfeit purchase intention. It was discovered that such individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 100 publications
(206 reference statements)
0
22
1
Order By: Relevance
“…Despite growing attention on the cultural differences in deliberate counterfeit purchase behavior (e.g., Eisend, 2019;Khandeparkar and Motiani, 2018;Li et al, 2018;Molina-Castillo et al, 2021;Tunçel, 2021;Wu et al, 2019), there are fewer studies on the role of individual-level cultural factors (e.g., Eisend et al, 2017;Kim and Johnson, 2014;Malik et al, 2020;Xiao et al, 2018). For example, Kim and Johnson (2014) examine the moderating role of individuals' independent (vs. interdependent) self-view in the relationship between moral emotions and judgments about the counterfeit purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Despite growing attention on the cultural differences in deliberate counterfeit purchase behavior (e.g., Eisend, 2019;Khandeparkar and Motiani, 2018;Li et al, 2018;Molina-Castillo et al, 2021;Tunçel, 2021;Wu et al, 2019), there are fewer studies on the role of individual-level cultural factors (e.g., Eisend et al, 2017;Kim and Johnson, 2014;Malik et al, 2020;Xiao et al, 2018). For example, Kim and Johnson (2014) examine the moderating role of individuals' independent (vs. interdependent) self-view in the relationship between moral emotions and judgments about the counterfeit purchase.…”
Section: Introductionmentioning
confidence: 99%
“…In these circumstances, the communicator is afraid the recipient will feel they have been given poor advice. Research has also found that communicating things that diverge from social norms entails social risk, such as displaying unusual product choices (Campbell & Goodstein, 2001), buying counterfeit products (Malik et al, 2020), or expressing unpopular opinions in face-to-face contexts (Schlosser, 2009). However, these results contradict Lin and Fang's (2006) study, which found that as the social risk of a product increases, there is more WOM about it.…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…Apart from the above 8 dominant theories that have been applied, there are 31 other theoretical lenses such as complexity theory , regulatory focus theory , just world theory , social bonding theory , socio intuitionist theory , and so forth, that have been employed in consumer ethics research. While most of the research have tested these theories in isolation (e.g., Gamma et al, 2020; Leischnig & Woodside, 2019; Peloza et al, 2013), but some studies have integrated two or more theories in their research framework (e.g., Malik et al, 2020; Wirtz & McColl‐Kennedy, 2010; Zollo et al, 2018). Finally, 34% (36/106) studies did not mention the application of any theory in their research.…”
Section: Synthesis and Findingsmentioning
confidence: 99%
“…Additionally, Escadas et al (2020), examined how postdecision emotions mediate the relationship between ethical decision‐making and “future ethical behavioural intentions.” Firm‐related mediating factors include relationship quality and outcome (Chang & Lu, 2019), trust in ethical advertising (Osburg et al, 2020), trust in product information (Osburg et al, 2020). Likewise, social and interpersonal factors such as benefits from the FB community (Gummerus et al, 2017), susceptibility to normative influence (Malik et al, 2020) coping factors like moral disengagement (Chowdhury & Fernando, 2014), deterrence factors like perceived risk (Zhao et al, (2020) and other factors like perceived justice (Septianto et al, 2020), implementation plans (Grimmer et al, 2016) have also been investigated as mediators. Overtime a rise in exploring mediation mechanisms is evident, as 66% of the mediation‐related studies were conducted in the last 3 years.…”
Section: Synthesis and Findingsmentioning
confidence: 99%
See 1 more Smart Citation